Planetary accounting quantifying how to live within planetary limits at different scales of human activity - Meyer, Kate; Newman, Peter 1945- (Springer Nature, 2020)
This book presents a novel way to enable people, regardless of their scale of influence, to take responsibility for global environmental problems including climate change. It introduces a new framework called Planetary Accounting, which allows the Planetary Boundaries, non-negotiable limits for the environment, to be translated into limits for human activity. It shows how such limits can be broken down into chunks that can be managed at different levels (from individual and community, to business and sector levels, to cities and regions), and at any level of government. The book begins by summarising the science of climate change and introducing the notion of the Anthropocene the human age. It highlights the importance of returning to and remaining within the Planetary Boundaries but shows that we cant realistically do so unless we have a new approach to environmental accounting. The book then outlines how Planetary Accounting furnishes this new approach by combining sustainability science, change theory, and environmental accounting to create a scalable framework for environmental management that encourages systemic and individual change. The details of the science of and our human contribution to ten critical human pressures are then presented, and the book concludes with a guide for those seeking to apply Planetary Accounting in practice. Planetary Accounting could form the scientific underpinning of behaviour change programs, guide the development of policy and regulations, and provide both the basis for environmental laws, and the foundation of future global environmental agreements. It has been 50 years since the first views from space showed a blue planet alone in our solar system. This book is an historic opportunity to provide humanity for the first time with sufficient information to begin implementing Planetary Accounting
Keywords: Verantwortung; Klimaänderung; Nachhaltigkeit; Verhaltensmodifikation; Umwelt; Environmental auditing; Environmental responsibility; Business enterprises / Environmental aspects